Respuesta :

To solve expressions like the one above, you must first complete the operations inside the parenthesis. We know this because of PEMDAS, wherein the P (representing parenthesis) comes first.

(14 - 6) * (2+4) = (8) * (6)

Next, we must simplify the expression. There is only one operation left to complete, multiplication, so that is what we are going to do next.

8 * 6 = 48

Therefore, your answer is B. 48

I hope this helps! :)
Photon
(14-6) x (2+4)
= 14 x 2 + 14 x 4 - 6 x 2 - 6 x 4
= 28 + 56 - 12 - 24
= 48

Therefore the answer would be : B. 48.

Hope this helps !

Photon
ACCESS MORE